Learning from Dora the explorer: Engaging children to the concept of bilingualism (paper review) - Widayanthi, Desak Gede Chandra (Journal of Language, Literature, Social and Cultural Studies, 2023)
This paper aims at finding the impact of TV shows on bilingualism. However, the analysis would be limited to one educational TV show which has been well-known worldwide: Dora the Explorer. This paper is a library research, in which the data were gathered from the related sources. The data then was described in a qualitative description. As the result, it could be concluded that Dora the Explorer was intended to create create a show that would teach children problem-solving skills and make viewers active participants in the events. Besides the interactive element of the series, its further characteristic feature is bilingualism, which is presented in every episode. The bilingual element is presented in the show because the designer of the show believes that introducing a second language to children before the age of 6 or 7 is crucial in assisting them to achieve fluency in the second language. The effect has been proven by research conducted by Länkinen (2013), which aimed at analyzing the impact of watching certain didactic programs in Dora the Explorer (which is in Finnish called as Seikkailija Dora). From the research, it is found that children who watch Dora the Explorer as a supplement to their learning, have a wider range of vocabulary compared to those who did not watch the TV show.